The Implementation of Projek Penguatan Profil Pelajar Pancasila through The Sasak Heritage Collage Activity in Elementary Schools - Nurwahidah Nurwahidah; Setiani Novitasari; Iva Nurmawanti; Ketut Sri Kusuma Wardani; Prayogi Dwina Angga (Postgraduate, University of Mataram, 2023)
This study aimed to determine the practicality of implementing the Projek Penguatan Profil Pelajar Pancasila through the Sasak Heritage Collage activity in elementary schools. The research was conducted in SD Negeri 36 Cakranegara during the odd semester of the 2023/2024 academic year, with data collected from one teacher and 22 students. Descriptive quantitative analysis was performed on the data using implementation sheets, as well as teacher and student response questionnaires. The research findings indicated that: (1) The implementation of Projek Penguatan Profil Pelajar Pancasila through the Sasak Heritage Collage activity was successful in each of the following activities: a) activities investigating Sasambo cultural diversity such as language, traditional houses, and traditional clothing, with an implementation percentage of 84.72%; b) activities investigating Sasambo cultural diversity such as traditional cuisine and dance, with an implementation percentage of 88.89%; c) Sasak heritage collage activity, with an implementation percentage of 100%; and d) presentation activities resulting from Sasak cultural collages, with an implementation percentage of 75.56%. (2) The practicality of implementing the Projek Penguatan Profil Pelajar Pancasila through the Sasak Heritage Collage activity was deemed very practical, with a practicality percentage of 93.75% for teachers and 87.61% for students